Hedgehog signaling is a promising target for the treatment of hepatic fibrogenesis: a new management strategy using itraconazole-loaded nanoparticles - Elmorsy, Elsayed A.; Saber, Sameh; Kira, Ahmed Y.; Alghasham, Abdullah; Abdel-Hamed, Mohamed R.; Amer, Maha M.; Mohamed, Enas A.; AlSalloom A., A; Alkhamiss, Abdullah S.; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; Ellethy, Abousree T.; et al. (Frontiers in Pharmacology, 2024)
Liver fibrosis is a disease with a great global health and economic burden. Existing data highlights itraconazole (ITRCZ) as a potentially effective anti-fibrotic therapy. However, ITRCZ effect is hindered by several limitations, such as poor solubility and bioavailability. This study aimed to formulate and optimize chitosan nanoparticles (Cht NPs) loaded with ITRCZ as a new strategy for managing liver fibrosis. ITRCZ-Cht NPs were optimized utilizing a developed 22 full factorial design. The optimized formula (F3) underwent comprehensive in vitro and in vivo characterization. In vitro assessments revealed that F3 exhibited an entrapment efficiency of 89.65% ± 0.57%, a 169.6 ± 1.77 nm particle size, and a zeta potential of +15.93 ± 0.21 mV. Furthermore, in vitro release studies indicated that the release of ITRCZ from F3 adhered closely to the first-order model, demonstrating a significant enhancement (p-value < 0.05) in cumulative release compared to plain ITRCZ suspension. This formula increased primary hepatocyte survival and decreased LDH activity in vitro. The in vivo evaluation of F3 in a rat model of liver fibrosis revealed improved liver function and structure. ITRCZ-Cht NPs displayed potent antifibrotic effects as revealed by the downregulation of TGF-β, PDGF-BB, and TIMP-1 as well as decreased hydroxyproline content and α-SMA immunoexpression. Anti-inflammatory potential was evident by reduced TNF-α and p65 nuclear translocation. These effects were likely ascribed to the modulation of Hedgehog components SMO, GLI1, and GLI2. These findings theorize ITRCZ-Cht NPs as a promising formulation for treating liver fibrosis. However, further investigations are deemed necessary.